TREND PENELITIAN KEMAMPUAN LITERASI SAINS MAHASISWA DI PERGURUAN TINGGI: SYSTEMATIC LITERATURE REVIEW - Rozi, Fahrur; Molliq Rangkuti, Yullita; Surya, Edy (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2024)
Based on data released by Central Connecticut State University in 2016 with the title World's Most Literate Nations, stating that Indonesia ranks 60th out of 61 countries in terms of literacy skills, it can be said that literacy skills in Indonesia are still very minimal. Indonesia has a "Literacy Emergency". Research on science literacy is mostly done at the primary and secondary education levels while for higher education research is still not significant. So that this research aims to be related to the trend of science literacy research in higher education. The method used is a systematic literature review taken from national and international journals. Searching for literature sources in this article through the ERIC database and Google Scholar in 2022-2023. From the results of the search for literature articles obtained 25,480 consisting of ERIC there are 7493 titles and from Google Scholar 21,000 titles with the keywords Science Literacy and Science Literacy. Then using the exclusion criteria by looking at the publication time of the last 1 year (2022-2023) and the suitability of research in higher education obtained 571 articles consisting of ERIC there are 29 titles and from Google Scholar 600 titles. Then at the final stage an assessment was carried out by selecting journals with the same title and author, then limiting the year of publication, the scope of higher education and completeness obtained 14 literature, consisting of 11 literature in Indonesian and English.